Vortex Identification in the Flow Field of Opposed Jet Occupied Enclosure Space - 卢浩阳; 王聪聪; 陈红兵; 张岩; 李春阳; 刘宇航; 赵立国 (Zhileng xuebao)
In a occupied enclosure space formed by multiple opposed jet outlets, understanding the vortex structures plays a crucial role in controlling the spread of viruses and pollutants. This study constructed a scaled model of a occupied enclosure space with opposing jet flows, incorporating a heated floor as a heat source to create thermal plumes under cooling conditions. Particle Image Velocimetry (PIV) system was employed to measure the flow field under isothermal and cooling conditions. Studying the Turbulent Characteristics of the Flow Field from the Vortex Perspective, comparing the identification performance of different vortex identification algorithms. The Liutex vortex identification method was applied to analyze the vortex motion within one oscillation period, revealing distinct strengths in counterclockwise and clockwise directions, with maximum intensities of 50 and 110 s?1, respectively. The study concluded that the motion, merging, and annihilation of vortices influence the flow field structure, with a jet oscillation period of approximately 3.67 seconds. Due to the trapping effect of vortexes on pol-lutants, areas of pollutant accumulation can be represented through the vortex core relative frequency distribution maps. It is observed that, despite the flow field being unsteady, the distribution of vortexes remains relatively stable. Specifically, on the left side of the CS4 cross-section, the vortex core appeared at the same point up to 21 times. Under cooling con-ditions, pollutants are confined to smaller regions, which aids in containing the spread of pollutants.